A New Agile Radiating System Called Electromagnetic Band Gap Matrix Antenna - Hussein Abou Taam; Moustapha Salah Toubet; Thierry Monediere; Bernard Jecko; Mohammad Rammal (International Journal of Antennas and Propagation)
Civil and military applications are increasingly in need for agile antenna devices which respond to wireless telecommunications, radars, and electronic warfare requirements. The objective of this paper is to design a new agile antenna system called electromagnetic band gap (EBG) matrix. The working principle of this antenna is based on the radiating aperture theory and constitutes the subject of an accepted CNRS patent. In order to highlight the interest and the originality of this antenna, we present a comparison between it and a classical patch array only for the (one-dimensional) 1D configuration by using a rigorous full wave simulation (CST Microwave software). In addition, EBG matrix antenna can be controlled by specific synthesis algorithms. These algorithms use inside their; optimization loop an analysis procedure to evaluate the radiation pattern. The analysis procedure is described and validated at the end of this paper.